Efficacy of Hydroxychloroquine for Improving Pregnancy Outcomes in a Female with Systemic Lupus Erythematosus and Antiphospholipid Syndrome. (21st August 2022) - Takaki, Yumika; Daimon, Atsushi; Nunode, Misa; Tanaka, Tomohito; Fujita, Daisuke; Ohmichi, Masahide
Abstract : The use of heparin and low-dose aspirin is the current conventional treatment for pregnant females with antiphospholipid syndrome (APS). However, there is no additional treatment recommended for cases where the standard treatment cannot prevent obstetric complications such as fetal loss and placental insufficiency. Recently, the addition of a novel antimalarial, hydroxychloroquine (HCQ), to the conventional treatment has shown the potential to prevent obstetric complications. Herein, we report a case in which the addition of HCQ improved adverse pregnancy outcomes in a pregnant female with systemic lupus erythematosus and aspirin-heparin-resistant APS.